Factor influences selection of Islamic banking: a study on Malaysian customer preferences - Haque, A. K. M. Ahasanul; Osman, Jamil; Ismail, Ahmad Zaki (Science Publications, 2009)
The emergence of strong Islamic movements in last three decades has generated a renewed interest in Islamic economics, especially in Islamic interest free banking. Currently Islamic bank strategically offering high quality products and services to satisfy their customers due to the strong competition, customer expectation for high quality services and rapidly changes of technology. The purpose of this study is to investigate major factors that are reflecting to customers’ perception and satisfaction on Islamic banking. This study hope to analyze and determine the perception, quality of services, availability of services, confidence in bank and social and religious perspective about Islamic banking system. A Logit model is employed to anticipate the effects of the explanatory variables. The analysis confirms the significant positive relationship of quality of services, availability of services, social and religious perspective and confidence in bank with customers’ perception about Islamic bank. These factors are expected to have great role for influencing customer mind. In conclusion, customers can derive a better understanding of the activities that are undertaken by bank and how the way these activities are being dealt with.